Mediasi Determinan Keberlanjutan Usaha Dengan Kinerja Pada Pelaku UMKM di Kota Bima - Pratiwi, Aliah; Nurulrahmatiah, Nafisah (Politeknik Ganesha Medan, 2024)
The purpose of this study is to determine the direct relationship between financial literacy, digital literacy and financial inclusion on the performance of MSMEs. As well as the indirect relationship between financial literacy, digital literacy and financial inclusion on the sustainability of MSMEs through performance. This research uses a quantitative approach method by distributing questionnaires. The population in this research is all MSMEs in Bima City. The sampling technique used is random sampling, namely random sampling based on a predetermined sample. The total sample was 100 respondents with a distribution of 20 respondents each in 5 sub-districts. The data analysis tool uses Smart PLS. The results of this research provide information that financial literacy, digital literacy and financial inclusion have an influence on the performance of MSMEs. Likewise, with indirect effects, the results show that financial literacy, digital literacy and financial inclusion influence the sustainability of MSMEs through performance.